Osteological morphometric analysis of instrumentation safe zones of C1 and C2 vertebra in North Indian population: a multicentric study - Gogia, Tushar; Dasgupta, Tirthankar; Goel, Neha; Singh, Narender; Rajan, Aravind; Das, Mainak; Khera, Dhairya (International Journal of Research in Orthopaedics, 2023)
Background: The complex anatomy and critical functional role of the C1 and C2 vertebrae necessitate precise understanding of safe zones for instrumentation to mitigate risks during surgical interventions. This study aimed to conduct a comprehensive morphometric analysis to identify and characterize safe zones for instrumentation within C1 and C2 vertebrae. Though there are multiple radiological based studies, actual osteological measurements are not available for North Indian population. Methods: 200 atlas and axis vertebrae were measured within an accuracy of 0.01 mm to ascertain various dimensions, distances and angles to guide safe exposure and instrumentation. To the best of our knowledge this observational morphometric study is first to provide actual osteological measurements in large number of C1 and C2 vertebrae in North Indian population. Results: The morphometric analysis revealed precise measurements of pedicle dimensions, transverse foramen parameters, and distances from key anatomical landmarks within C1 and C2 vertebrae. Safe zones for instrumentation were identified based on these measurements, considering the optimal implant size and trajectory to minimize the risk of neural or vascular damage. Differences between the morphology of North Indian, South Indian and Turkish C1 and C2 morphology was also identified. Conclusions: This study provides critical insights into the morphometric parameters which can be used to identify safe zones for instrumentation within the C1 and C2 vertebrae. The identified safe zones and associated measurements are essential for optimizing surgical strategies, enhancing instrumentation accuracy, and ultimately improving patient outcomes during craniovertebral surgical procedures. Spine Surgeons can utilize this data to tailor surgical approaches and implant placements, promoting safer and more effective interventions in the challenging anatomical region of the craniovertebral junction.